2008
DOI: 10.1002/jmv.21087
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of RS‐12 (S‐12), an Iranian isolate of mumps virus, by sequence analysis and comparative genomics of F, SH, and HN genes

Abstract: RS-12 mumps virus strain was isolated in 1986, in monkey kidney cells, from the throat-washing of an Iranian patient and developed to RS-12 vaccine by serial passage of the pathogen in MRC-5 cells. During the present study, an early passage RS-12 containing its virulent pathogenic phenotype, was characterized genetically. Its F, SH and HN genes were isolated by RT-PCR amplification and sequenced. It is quite evident that RS-12 belongs to genotype H, closely related to European strains but distinguishable from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…This is the first report of a mumps genotype in Southwest Iran and is different from the RS 12 strain (genotype H) which was reported in 1986, in Tehran. [45] In this study, the SH region of genotype N (KT346350 and KT346351) showed amino acid substitutions at positions 9(Y→H), 29(I→T), 42(A→T), 44(H→Y), and 56(S→P) compared with the RS 12 (genotype H) strain. The amino acids at positions 29 and 48 of the SH region are important due to their effect on virus attenuation, especially when substitutions occur simultaneously.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This is the first report of a mumps genotype in Southwest Iran and is different from the RS 12 strain (genotype H) which was reported in 1986, in Tehran. [45] In this study, the SH region of genotype N (KT346350 and KT346351) showed amino acid substitutions at positions 9(Y→H), 29(I→T), 42(A→T), 44(H→Y), and 56(S→P) compared with the RS 12 (genotype H) strain. The amino acids at positions 29 and 48 of the SH region are important due to their effect on virus attenuation, especially when substitutions occur simultaneously.…”
Section: Discussionmentioning
confidence: 68%
“…[19] The SH region is the most variable part of the genome and is used for genotyping as well as for phylogenetic analysis of the virus. [44,45] In this study, about 316 nucleotides of the SH and the first 162 nucleotides of the intravirion and transmembrane domains of the HN gene were sequenced. Their amino acid sequences were aligned and compared with wild type and vaccine strains in the gene bank.…”
Section: Discussionmentioning
confidence: 99%
“…Although some structural and functional changes due to substitution of Leucine with Proline (for instance addition/deletion of a glycosylation site or formation/wrapping an epitope due to conformational changes in HN protein) could be expected, amino acid 138 is not among those motifs that previously have described as functional motifs in HN gene (3,16). In addition, homology modeling analysis suggested that this mutation has occurred in a relatively variable region of HN protein.…”
Section: Discussionmentioning
confidence: 89%
“…Following verification of amplification program, pfu polymerase was used to amplify viral cDNA. Since the HN and F genes are relatively long, two pairs of specific primers (which previously had been designed based on highly conserved sequences) were synthesized by MWG (Germany) and used in amplification reactions (3). Since viral SH gene was short in length, amplification with one pair of specific primers were done (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Although this isolate has been partially characterized, a molecular basis for attenuation remains to be determined. Phylogenetic analysis based on the entire SH gene determined that the wild RS-12 strain pertained to the genotype H and was located within the European strains that compose an entirely separate cluster from the Far Eastern isolates (Alirezaie et al, 2008).…”
Section: Introductionmentioning
confidence: 99%